Investigating spatio-temporal variability of initial ²³⁰Th/²³²Th in intertidal corals - Chiang, Hong-Wei (2023)
One of the key factors in obtaining precise and accurate 230Th ages of corals, especially for corals with ages less than a few thousand years, is the correction for non-radiogenic 230Th based on an initial 230Th/232Th value (230Th/232Th0). Studies that consider coral 230Th/232Th0 values in intertidal environments are limited, and it is in these environments that corals have Th concentrations 100–1000 times greater than open-ocean corals. Here we present 66 reconstructed U–Th isochrons of modern and Holocene Porites lutea and lobata corals from throughout the Sumatran forearc islands (SFI). Mean square of weighted deviates (MSWD) is used to evaluate the variabilities of 28 location-specific 230Th/232Th0 values before the regional mean. Results show no significant spatial difference between the means of 3.1 ± 3.2 × 10−6 for the northern SFI and 4.7 ± 1.3 × 10−6 for the southern SFI. Using the weighted mean of 4.3 ± 2.5 × 10−6 for all islands has the advantage that no data need be subjectively excluded in the calculation of reliable 230Th ages, where a local initial value is unknown. There were no clear centennial to millennial time-scale changes in 230Th/232Th0 in the past 2500 years. This study, therefore, suggests a reliable value of initial 230Th/232Th ratio in intertidal environments.